De wondere wereld van de techniek - Schot, J. (BMGN - Low Countries Historical Review, 2008)
Woud, A. van der. Een nieuwe wereld. Het ontstaan van het moderne Nederland (Amsterdam 2006) The Wonderful World of TechnologyTechnology shapes history. The transport and communication infrastructures in particular contributed towards the development of the nation state during the second half of the nineteenth century. Van der Woud has written a rich history on this subject illustrating how the development of an infrastructure forced the newly established Dutch state to redefine the public and the private sector, and in so doing itself, which in turn led to the emergence of an imagined community of the Netherlands. His account is less convincing when it attempts to explain the origins of this infrastructural revolution. He refers to a new vision of civilization but forgets to place it more precisely in its social and political context. This is mainly due to his sources. His primary source, trade journals, allow him to give a fascinating account of the magical power experienced through the new technologies, but fall short of helping him to portray how far, and in which ways, different bodies in the Netherlands have steered the development. This review is part of the discussion forum 'Een nieuwe wereld' (A. van der Woud).